Triple-controlled oncolytic adenovirus expressing melittin to exert inhibitory efficacy on hepatocellular carcinoma - Qian, Chun-Yu (Int J Clin Exp Pathol, 2015)
Hepatocellular carcinoma (HCC) is a highly malignant disease, and its outcome of routine therapies is poor. Comprehensive treatment including gene therapy is an important way to improve patients’ prognosis and survival. In this study, we successfully constructed a triple-controlled cancer-selective oncolytic adenovirus, QG511-HA-Melittin, carrying melittin gene, in which the hybrid promoter, hypoxia-response element (HRE)-AFP promoter, was used to control viral E1a expression targeting AFP-positive cancer cells in hypoxia microenviroment, and the E1b-55 kDa gene was deleted in cancer cells with p53-deficiency. The cytological experiments found that the viral replication of QG511-HA-Melittin was increased to 12800-folds in Hep3B cells within 48 h, and 130-folds in SMMC-7721, but the virus did not replicate in L-02 cells. QG511-HA-Melittin had a strong inhibition effect on AFP-positive HCC cell proliferation, such as Hep3B and HepG2, whereas, there was low or no inhibition effect of QG511-HA-Melittin on AFP-negative cancer cells SMMC-7721 and normal cells L-02. In the in vivo experiment, compared with the blank control group, QG511-HA-Melittin can significantly inhibit the growth of HCC xenografts (P<0.05). The survival of mice in QG511-HA-Melittin group was much longer than that of the blank control group. Both in vitro and in vivo experiments manifested that QG511-HA-Melittin exerts an inhibitory effect on HCC cells, which may provide a new strategy for HCC biotherapy.